Efektivitas Penerapan Hukum Perlindungan Perempuan Dan Anak Dalam Mencegah Kekerasan - Indah Anugerah Sidik; Asep Suherman (CV. ITTC INDONESIA, 2024)
Violence against women and children is a serious problem that still occurs in Indonesia, despite regulations designed to protect these vulnerable groups. Law No. 23/2004 on the Elimination of Domestic Violence (PKDRT) and Law No. 35/2014 on Child Protection provide a strong legal foundation, but their implementation often faces challenges. The main legal issue in this study is how the implementation of laws on the protection of women and children can be effective in preventing violence, and what factors influence this effectiveness. This paper aims to analyze the application of the law and identify obstacles in its implementation. The method used in this research is the normative juridical method, by analyzing relevant legislation. The results show that although the law on the protection of women and children is available, its implementation is still constrained by a lack of socialization, low law enforcement, and cultural barriers that prevent victims from reporting. Therefore, improvements are needed in the implementation of the law to make it more responsive and effective in protecting women and children from violence.